Hepatitis C Virus Infection Associated With an Increased Risk of Deep Vein Thrombosis. Issue 38 (September 2015) - Wang, Chun-Cheng; Chang, Chiz-Tzung; Lin, Cheng-Li; Lin, I-Ching; Kao, Chia-Hung; Liu., Miao
<x xml:space="preserve">Abstract</x> Abstract The association between the hepatitis C virus (HCV) infection and the risk of myocardial infarction (MI) and stroke has been previously investigated. However, the association between the HCV infection and the risk of venous thromboembolism (VTE) has not been extensively discussed. Using the Longitudinal Health Insurance Database 2000 (LHID2000), we selected 3686 patients with newly diagnosed HCV infection. We randomly selected 14, 744 people with no HCV or hepatitis B virus (HBV) infection as comparison group and frequency matched them with patients with HCV infection according to their age, sex, and index year. The incidence density rates and hazard ratios (HRs) of deep vein thrombosis (DVT) and pulmonary embolism (PE) were calculated until the end of 2011. The mean follow-up duration of 5.14 years for the HCV cohort and 5.61 years for the non-HCV cohort, the overall incidence density rates of DVT were 7.92 and 3.51 per 10, 000 person-years in the non-HCV group, and the HCV groups, respectively (crude HR = 2.25; 95% confidence interval [CI] = 1.21–4.21). After adjusted for age, sex, and comorbidities, the risk of DVT remained significantly higher in the HCV group than in the non-HCV group (adjusted HR = 1.96; 95% CI = 1.03–3.73). The overall incidence density rates of PE in the HCV and non-HCV groups were not significantly different (crude HR = 2.20; 95% CI = 0.94–5.14). HCV infection is associated with the risk of DVT in a long-term follow-up period.